Transcriptional Responses in the Murine Spleen after Toxoplasma gondii Infection: Inflammasome and Mucus-Associated Genes - Znalesniak, Eva B. (Int J Mol Sci, 2017)
The spleen plays an important role in coordinating both adaptive and innate immune responses. Here, the transcriptional response to T. gondii infection in the murine spleen was characterized concerning inflammasome sensors (two different models: seven days after oral or four weeks after intraperitoneal infection). Additionally, Tff1(KO) and Tff3(KO) mice were investigated because TFF genes are often upregulated during inflammation. The expression of the pattern-recognition receptors Nlrp3, Nlrp12, and Nlrp1a was significantly increased after infection. This increase was diminished in Tff1(KO) and Tff3(KO) mice pointing towards a positive regulation of the inflammatory response by Tff1 and Tff3. Furthermore, the transcription of Tff1 (encoding a motogenic lectin) and other secretory genes was analyzed, i.e., gastrokines (Gkn), IgG Fc binding protein (Fcgbp), and the mucin Muc2. The corresponding gene products belong to an interactome protecting mucous epithelia. Tff1 was significantly induced after infection, which might increase the motility of immune cells. In contrast, Gkn3, Fcgbp, and Muc2 were downregulated seven days after oral infection; whereas four weeks after i.p. infection only Gkn3 remained downregulated. This might be an indication that Gkn3, Fcgbp, and Muc2 are involved in the transient disruption of the splenic architecture and its reorganization, which is characteristic after T. gondii infection.